ANALISIS PRIORITAS PENGENDALIAN RISIKO PELAKSANAAN PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI PROVINSI SUMATERA UTARA - Dinnie Ananda Rizky; Suprapto Siswosukarto; Ashar Saputra (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2022)
BSPS is a community-based program in the housing sector for improving basic service infrastructure and increasing access to decent, safe and affordable housing and settlements for low-income communities in Indonesia, including the Province of North Sumatera. In 2020, the  amount of housing assistance that Province of North Sumatera received  in improving the quality of houses was 7,077  allocations in 15 districts/cities. For this reason, it is necessary to carry out the further analysis of risk control in program implementation as a benchmark for development in accordance with the government's objectives in reducing uninhabitable houses in Indonesia. This research used descriptive quantitative method. The problem assessment was carried out using the Analytical Hierarchy Process (AHP) method to obtain the priority risk criteria from 18 appropriate sub-criteria. Based on the survey results from 3 expert respondents, it was found that the highest risk control priorities were individual or collective aspirations of 27.02%, community understanding of livable housing (RLH) 12.68%, and competence of the facilitator 8.91%.